Implementasi Pendaftaran Hak Tanggungan Secara Sistem Elektronik - Saputra, Tri Eka (Jurnal Litigasi Amsir, 2022)
This article describes mortgage services in an electronic system in Indonesia as an effort to improve the quality of public services in the land sector by utilizing modern integrated information technology. This article examines the implementation of Mortgage services in an electronic system. The method used is normative juridical research with a statutory approach. The results of this study indicate that: The implementation of electronic mortgage services in Indonesia is in accordance with the Minister of Agrarian Affairs, which specifically requires electronic registration of mortgage rights on the website of the Minister of Agrarian Affairs and Spatial Planning/Head of the Land Agency.